Direct visualization of the phenotype of hypoxic tumor cells at single cell resolution in vivo using a new hypoxia probe. Issue 2 (3rd May 2016) - Wang, Yarong; Wang, Haoxuan; Li, Jiufeng; Entenberg, David; Xue, Alice; Wang, Weigang; Condeelis, John
ABSTRACT: Tumor hypoxia is linked to tumor progression, metastasis, and therapy resistance. However, the underlying mechanisms behind this linkage are not fully understood. Here we present a novel fluorescent mCherry hypoxia-responsive marker that can be used in real time imaging to specifically and sensitively identify hypoxic cells in vivo at single cell resolution. Tumors derived from triple negative tumor cells expressing the hypoxia marker reveal that the hypoxic tumor cells congregate near flowing blood vessels. Using multiphoton microscopy, hypoxic MDA-MB-231 cells were directly visualized and showed a more persistent slow migration phenotype as compared to normoxic cells in the same field in vivo. Hypoxic tumor cells are enriched in the cell population that migrates toward human epithelial growth factor gradients in vivo, and has increased collagen degradation and intravasation activity, characteristics of dissemination and metastasis competent tumor cells. The hypoxia probe introduced in this study provides a specific reporter of hypoxic cell phenotypes in vivo which reveals new insights into the mechanisms by which hypoxia is linked to metastasis.